Ventriloquial Acts: Critical Reflections on the Art of Foley. Issue 2 (September 2015) - Lewis, Matt
<x content-type="archive" xml:space="preserve">Abstract</x> Foley, the art of producing additional sound effects in synchrony to actions on screen, only forms a part of the use of sound effects in a film. It is akin to other 'dark arts' such as ventriloquism as it relies on the same manipulations of context and space. Because Foley perceptually links us to human gesture it offers a particularly useful model with which to understand not only cinematic reception but also our relationship with everyday sounds and music making. Although within the artificial environment of the cinema our perception is often played with and distorted, the controlled context of cinema is a useful laboratory in which to examine our responses to sound. This is a context from which we can develop a deeper understanding of our reception of sound outside of the cinematic realm. The text below uses our responses to the production of sound effects and in particular Foley, to examine critically different, and sometimes converging, strands of thinking around perception, listening practice, audiovisual theory and music.